Optimization of stable genetic transformation protocol in castor (Ricinus communis L. cv. TMV 5) using beta glucuronidase reporter gene for pioneer of desirable genes - Kumari, K. Ganesh; Jayabalan, N. (Current Botany, 2024)
The simple and stable protocol was standardised for castor (Ricinus communis L. cv. TMV 5) genetic transformation using Agrobacterium tumefaciens strain LBA4404 harbouring the binary plasmid pBAL2 (18.8 kb). Cotyledonary nodes from ten days old, in vivo seedlings were utilized as target cells for Agrobacterium mediated transformation. Explant pre-culture studies were carried out at 2, 4, 6, 8, 10 and 12 day intervals. The 4th day old explants cultivated on mMS medium (MS medium+B5 Vitamins) using plant growth regulators had the highest response percentage (50.6%). Kanamycin (0-175 mg/L) and Hygromycin (0-13 mg/L) sensitivity in well-developed shoots was investigated. Of the two antibiotics, Kanamycin 50 mg/L and Hygromycin 3 mg/L was found optimum. Different levels of acetosyringone (0-200 mg/L) were used in the co-cultivation medium to study the transformation efficiency of castor. Among the different concentrations, maximum number of explants showed GUS expression at 100 mg/L of acetosyringone in the co-cultivation medium at 2 days of co-cultivation period and the Cotyledonary node produced multiple shoots development and plantlet establishment in 0.3 mg/L TDZ, 0.6 mg/L PF-68, kanamycin 50 mg/L, 0.3 mg/L GA3, 1.5 mg/L IBA and 0.6 mg/L AgNO3. The rooted shoots were successfully acclimatized. Histochemical GUS assay was used to monitor T-DNA delivery into the target cells. PCR and Southern hybridization were used to confirm the transformants with the NPT II and GUS gene. A very high frequency (29.3%) of β-glucuronidase (GUS) gene expression was obtained through Agrobacterium-mediated gene transfer into cotyledonary node explants of Castor. The standardized protocol would be useful for Agrobacterium-mediated genetic transformation of Cator with desirable gene of agronomic importance.